URGENSI PENGEMBANGAN MODEL PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN PEADAGOGICAL CONTENT KNOWLEDGE MAHASISWA CALON GURU AGAMA PADA FAKULTAS TARBIYAH DI PERGURUAN TINGGI AGAMA ISLAM - Abdurrahmansyah Abdurrahmansyah; Ishak Abdulhak (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2012)
Educational challenges requires the improvement of the quality of learning.one of the challenges of learning in teacher education institutions is theweak development of prospective teachers. Shulman mentions that to improve thequality of learning for candidate teachers is through the concept of pedagogicalcontent knowledge (PCK). Tarbiyah Faculty as LPTK that prepares prospectivecandidate teachers of religion is considered important to seek the mastery of PCK skills through the development model of learning offered at the lecturing session. One of the benefits of PCKconcept is to be able to build the integrity of the candidate teacher’s competencies in mastering the content and pedagogy as a whole. The concept of PCK presents to overcome the problem of incompleteness of thecurriculum presentation that presents the content aspect on the one hand andaspects of pedagogy on the other side of other split aspects.